Działalność Komisji Badań nad Antykiem Chrześcijańskim TN KUL w roku akademickim 2022/2023 - Wilk, Piotr (Vox Patrum, 2023)
The report contains a description of the activities of the Committee for Research on Christian Antiquity of the Catholic University of Lublin in the academic year 2022/2023. The speakers of individual meetings were listed and the topics of individual meetings were summarized.